Response of transient rock uplift and base level knickpoints to erosional efficiency contrasts in bedrock streams. Issue 10 (19th May 2021) - Wolpert, Joshua A.; Forte, Adam M.
Abstract: Knickpoints in bedrock streams are often interpreted as transient features generated by a change in boundary conditions. It is typically assumed that knickpoints propagate upstream with constant vertical velocities, though this relies on a stream being in erosional steady state (erosion rate equals rock uplift rate) prior to the knickpoint's formation. Recent modeling and field studies suggest that along‐stream contrasts in rock erodibility perturb streams from erosional steady state. To evaluate how contrasts in rock erodibility might impact knickpoint interpretations, we test parameter space (rock erodibility, rock contact dip angle, change in rock uplift rate) in a one‐dimensional (1D) bedrock stream model that has variable rock erodibility and produces a knickpoint with a sudden change in rock uplift rate. Upstream of a rock contact, the vertical velocity of a knickpoint generated by a change in rock uplift rate is strongly correlated with how the rock contact has previously perturbed erosion rates. These knickpoints increase vertical velocity upon propagating upstream of a hard over soft contact and decrease vertical velocity upon propagating upstream of a soft over hard contact. However, interactions with other transient perturbations produced by rock contacts make for nuances in knickpoint behavior. Rock contacts also influence the geometry of knickpoints, which can become particularly difficult to identify upstream of soft over hard rock contacts. Using our simulations, we demonstrate how a contact's along‐stream horizontal migration rate and cross‐contact change in rock strength control how much an upstream reach is perturbed from erosional steady state. When simulations include multiple contacts, the knickpoint is particularly prone to colliding with other transient perturbations and can even disappear altogether if rock contact dips are sufficiently shallow. Caution should be taken when analyzing stream profiles in areas with significant changes in rock strength, especially when rock contact dip angles are near the stream's slope. Abstract : Common assumptions of bedrock river profile evolution in response to changes in climate and tectonics are tested against numerical simulations that include non‐vertical contrasts in rock erodibility. Upstream of non‐vertical contacts, knickpoints formed from a change in rock uplift rate are found to have propagation rates and morphologies deviating from common assumptions. A contact's migration rate and change in substrate erodibility play key roles in setting the magnitude of these deviations.